An empirical investigation of risk-return relations in Chinese equity markets: Evidence from aggregate and sectoral data - Thomas C. Chiang; Yuanqing Zhang (International Journal of Financial Studies, 2018)
This paper investigates the risk-return relations in Chinese equity markets. Based on a TARCH-M model, evidence shows that stock returns are positively correlated with predictable volatility, supporting the risk-return relation in both aggregate and sectoral markets. Evidence finds a positive relation between stock return and intertemporal downside risk, while controlling for sentiment and liquidity. This study suggests that the U.S. stress risk or the world downside risk should be priced into the Chinese stocks. The paper concludes that the risk-return tradeoff is present in the GARCH-in-mean, local downside risk-return, and global risk-return relations.
Keywords: G11; G12; G15; 330; stock return; Chinese stock market; illiquidity; VaR; GARCH-M; downside risk